The nonlinear effects of digital finance on carbon performance: Evidence from China - Bing Zhou; Yu-Lan Wang; Bin-Hu (Journal of Innovation & Knowledge, 2024)
To address global climate change and achieve high-quality development, China has to reach carbon peaking and carbon neutrality targets as objective requirements. Based on data from 30 Chinese provinces from 2011 to 2021, this study used a two-factor fixed effects and a mechanism model to test the effects and mechanisms of digital finance on carbon performance. The findings imply that the development of digital finance has a nonlinear effect of the ''first inhibit, then promote'' principle on carbon performance. Meanwhile, both the coverage breadth and usage depth of digital finance have a more significant impact on carbon performance. Digital financing can improve regional carbon performance through green technology innovation, industrial upgrades, and energy structure optimization. In addition, this effect exhibited significant heterogeneity. Specifically, the higher the level of marketization and the lower the urban–rural income gap, the more significant the nonlinear effect. The eastern region has the advantage of being rich in resources and technology, and the effect in the eastern region is more obvious compared to central and western regions. Therefore, China should accelerate the integration of financial services with modern digital technologies to achieve low-carbon development based on local conditions.